A Study on Effectiveness of Technical Academic Programs in Supporting Towards Lifelong Learning in a Technical University in Malaysia - Nor Hisham, Ghafar (2009)
The purpose of this study was to investigate the effectiveness of academic program towards supporting lifelong learning in a technical university in Malaysia. This study explored the relationship between various components in academic programs namely teaching and learning strategies, learning materials, role of instructors, course content, support system, and practical sessions; and students' attitude towards learning and their motivation to learn. A total of 263 students from semester 2 to semester 7 in eight academic programs were surveyed. The finding reveals that the students have good perceptions on each component of the academic programs and all those components have significant relationship with the students' attitude towards learning. It is also further learnt that the students' motivation to learn has a very strong positive connection with the students attitude towards learning.